Perkembangan media pembelajaran berbasis teknologi di era digital: Analisis urgensi penggunaan Artificial Intelligence di bidang pendidikan - Zainuddin, Zainuddin (Maliki Interdisciplinary Journal, 2023)
The improvement of innovation has benefits in working with crafted by educators and understudies. One of the innovations made by people is man-made consciousness (Computerized reasoning). Applications made to work with human work in the field of schooling are extremely assorted and fluctuated. The instances of utilizations made by people to assist with creating learning are Voice Colleagues, Virtual Tutors and Show Interpreters. The motivation behind this exploration is to dissect the utilization of Man-made brainpower in the field of Training as the advancement of learning media in the computerized time. This exploration is a Subjective Exploration utilizing the kind of Writing Survey Study. The information utilized in this study is optional information gotten from diary articles obtained from Google Researcher. The consequences of this study express that the earnestness of Man-made consciousness in the field of training can utilize a few applications made by people like Voice Colleagues, Virtual Coaches and Show Interpreters. The utilization of simulated intelligence in its application can be used by educators as learning media in the homeroom, one of the objectives is to take full advantage of innovation that has grown quickly and make man-made brainpower (Computerized reasoning) as Showing Collaborators in involving man-made intelligence as a learning medium and as an exit plan to work with understudies in learning.